2013
DOI: 10.1038/jid.2013.200
|View full text |Cite
|
Sign up to set email alerts
|

The Adherens Junction: A Mosaic of Cadherin and Nectin Clusters Bundled by Actin Filaments

Abstract: Summary Cadherin and nectin are distinct transmembrane proteins of adherens junctions. Their ectodomains mediate adhesion while their cytosolic regions couple the adhesive contact to the cytoskeleton. Both these proteins are essential for adherens junction formation and maintenance. However, some basic aspects of these proteins, such as their organization in adherence junctions, have remained open. Therefore, using super-resolution microscopy and live-imaging, we focused on the subjunctional distribution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 28 publications
5
73
0
Order By: Relevance
“…As we have shown previously, these cells form typical adherens junctions consisting of cadherin (E-and P-cadherins) and nectin-2 clusters (Indra et al, 2013). We have also shown that once these cells touch one another, cadherin and nectin clusters always appear at the same sites (Indra et al, 2014).…”
Section: E-cadherin Forms Junctions Faster Than Nectinmentioning
confidence: 48%
See 3 more Smart Citations
“…As we have shown previously, these cells form typical adherens junctions consisting of cadherin (E-and P-cadherins) and nectin-2 clusters (Indra et al, 2013). We have also shown that once these cells touch one another, cadherin and nectin clusters always appear at the same sites (Indra et al, 2014).…”
Section: E-cadherin Forms Junctions Faster Than Nectinmentioning
confidence: 48%
“…S2A). As in many other cell types (Indra et al, 2013), the nectin-containing adherens junctions were also positive for vinculin (Fig. 1D).…”
Section: E-cadherin Modulates the Formation Of Nectin-2 Junctionsmentioning
confidence: 86%
See 2 more Smart Citations
“…via catenins) and other transmembrane proteins (i.e. nectins [17], growth factors receptors and integrins). In spite of extensive progress in the identification of cytoskeletal proteins found at junctions [18,19], the precise F-actin organization and the specific actin remodelling functions at cadherin contacts lack in-depth understanding.…”
Section: Junctional Actinmentioning
confidence: 99%